2018
DOI: 10.31674/mjn.2018.v10i01.004
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Pain in Patients Undergoing Coronary Invasive Procedures in Trans-Radial Versus Trans-Femoral Approaches: A Cross-Sectional Study

Abstract: Trends for invasion site for coronary interventions are shifting from femoral to radial approach because of the advantageous effects. Assessment of pain associated with puncture site in both approaches (radial/femoral) is important. Purpose of this study is to find the difference in post procedural access site pain in patients undergoing coronary invasive procedures in trans-radial versus trans-femoral approach and its association with age, gender and BMI. A cross-sectional study was conducted with 75 randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A study carried out in Lahore in 2021 determined that those with post-angiography femoral access experienced more local pain and more discomfort compared to those with radial access. 15 In the study performed by Fens 12 (2015) in the Netherlands, patients who underwent both radial and femoral interventions were questioned, 2 vascular access routes were compared based on the patient's perspective, and no access route was found to be superior. It was indicated that the vascular access decision was a preference-sensitive decision and that the importance of the procedure's features might vary according to the patient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study carried out in Lahore in 2021 determined that those with post-angiography femoral access experienced more local pain and more discomfort compared to those with radial access. 15 In the study performed by Fens 12 (2015) in the Netherlands, patients who underwent both radial and femoral interventions were questioned, 2 vascular access routes were compared based on the patient's perspective, and no access route was found to be superior. It was indicated that the vascular access decision was a preference-sensitive decision and that the importance of the procedure's features might vary according to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions with radial artery access are preferred due to its aspects such as fewer complications at the site of access, early mobilization, early discharge, low cost, and improved quality of life. 11,12,15 Although many sources emphasize that transradial angiography increases success, reduces the time of procedure, and is preferred by patients, it has also been mentioned that its use is limited due to the length of the procedure and procedural failure. 15 Furthermore, treatment with transfemoral vascular access reported to bring higher cost of procedures, higher complication rates and longer time spent at hospital.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions with radial artery access are preferred due to its aspects such as fewer complications at the site of access, early mobilization, early discharge, low cost, and increased quality of life. 11,12,15 Although it is emphasized in many sources that transradial angiography increases success, reduces the procedure time, and is preferred by patients, it has also been mentioned that its use is limited due to the length of the procedure and procedural failure. 15 It has been demonstrated that the cost of procedures and the complication rate are higher, and the length of hospital stay is longer in patients treated with transfemoral vascular access.…”
Section: Introductionmentioning
confidence: 99%